2015
DOI: 10.1097/brs.0000000000000734
|View full text |Cite
|
Sign up to set email alerts
|

Single-Level Lumbar Fusion for Degenerative Disc Disease Is Associated With Worse Outcomes Compared With Fusion for Spondylolisthesis in a Workersʼ Compensation Setting

Abstract: 3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 19 publications
1
22
0
Order By: Relevance
“…These reports suggest that psychological and social factors should be considered before performing fusions. Outcome of fusion is generally not so good, and patients with workers' compensation have worse outcomes 84) . Low back pain was a good indication for fusion, but many contrast studies have indicated that superiority of fusion is not proved compared with exercise or cognitive behavioral treatment.…”
Section: Fusionmentioning
confidence: 99%
“…These reports suggest that psychological and social factors should be considered before performing fusions. Outcome of fusion is generally not so good, and patients with workers' compensation have worse outcomes 84) . Low back pain was a good indication for fusion, but many contrast studies have indicated that superiority of fusion is not proved compared with exercise or cognitive behavioral treatment.…”
Section: Fusionmentioning
confidence: 99%
“…The poor RTW outcomes in both the COT (11.0%) and TOT (38.4%) groups are in line with other studies citing low RTW rates after lumbar fusion among WC subjects. 14,16,[24][25][26][27][28] Additionally, the high rates of psychiatric disease after fusion and the strong impact depression had on rates of COT may indicate a possible impact of better screening and treatment for psychiatric disease before lumbar fusion. Also, the significantly greater use of psychotherapy after fusion between both groups may suggest worsening psychological health after fusion within our study population.…”
Section: Occupational Health/ergonomicsmentioning
confidence: 99%
“…7,9 Furthermore, lumbar fusion surgery for degenerative disc disease (DDD) and discogenic LBP also referred to as discogenic fusion, has been associated with variable clinical outcomes, particularly when compared with fusion for more definable instability, such as spondylolisthesis. [10][11][12][13][14][15][16][17][18] Some RCTs have reported significant improvement in Oswestry Disability Index (ODI) after discogenic fusion, but upon pooling data in a meta-analysis, Bydon et al recently reported no significant difference compared with nonoperative therapy. 18 DDD and discogenic LBP are estimated to now be the most common indications for lumbar fusion in the United States, as rates of discogenic fusion have increased approximately 220% since 1990.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[3] One study reported that patients undergoing fusion for spondylolisthesis had shorter periods of postoperative opioid pain reliever use and were more likely to return to work than were patients having fusion for DDD. [11] Figure 2. Lumbar spinal stenosis…”
Section: Spinal Stenosismentioning
confidence: 99%